ANALISIS PROGRAM “KANTIN KONTAINER” PADA DOMPET DHUAFA CABANG BENGKULU DALAM PENGURANGAN TINGKAT KEMISKINAN MUSTAHIK BERDASARKAN MODEL CIBEST - Alfiah, Esti (Al-Amwal : Journal of Islamic Economic Law, 2024)
Purpose—This study aims to analyze the empowerment of productive zakat on zakat mustachios at the institution “Dompet Dhuafa "Container Canteen" in the province of Bengkulu through the program in an effort to reduce poverty among mustachios by using the CIBEST model. Method– The method used in this research is field research with a descriptive quantitative approach. Data was collected through surveys and interviews with 10 mustahik involved in the program. This research took place from April to July 2024, with the research location in Bengkulu Province, specifically at mustahik business places that received assistance from the Dompet Dhuafa "Container Canteen" program which runs a poverty alleviation program with CIBEST (Center for Islamic Business and Economic Studies). Result– The distribution of zakat assistance through the "Container Canteen" with the CIBEST  model  has a positive impact on the income of mustahik households. Specifically, this program can reduce material poverty by 10% and improve the welfare of mustahik households by 47%. Although the spiritual poverty index did not change, there was a decrease in the number of mustahik households in Quadrants I and IV, indicating an improvement in their economic and spiritual conditions. Implication—Measure the welfare of mustahik using the scientific treasures related to the CIBEST model of productive zakat management. The Dompet Dhua'afa Institution can contribute thoughts and input regarding productive zakat management through its programs.